The Effect of Kick Training Model on Crescent Kick Ability in Pencak Silat Athletes (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of the Kick Training Model on the ability to perform a hook kick in male athletes of Pencak Silat Merpati Putih Medan Baru in 2025. The research method used is the experimental method. The sampling technique used involved 8 participants, and the study was conducted over 6 weeks with a training frequency of 3 times per week. Statistical calculations were performed using a t-test. Hypothesis analysis was conducted using pre-test and post-test data on kicking ability, where the calculated t-value was 4.554. This value was compared with the critical t-value with df = n - 1 (8 - 1 = 7) at a significance level of α = 0.05, which was 1.895. Thus, the calculated t-value was greater than the critical t-value (4.554 > 1.895). The research data showed that the pre-test average was 31.9 and the post-test average was 39. The data obtained were tested for normality and homogeneity. The data were normally distributed and homogeneous, followed by hypothesis testing using statistical tests via SPSS version 29. The sig. The value was 0.004. This sig. The value is smaller than 0.05. Therefore, Ho is rejected and Ha is accepted, concluding that there is a significant effect of the kicking training model on the crescent kick. The state of the art and novelty of this study is to improve the crescent kick ability in pencak silat using the implemented training model.